Kesadaran Hukum Petani Tambak Udang Vaname Muslim Dalam Menunaikan Kewajiban Zakat Maal - Khomsatun, Dede; ., Mubarok (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Vaname shrimp farming is very promising, with a net income in one harvest that can reach 80 million if successful. However, the majority of farmers do not issue pond zakat, but some are only giving alms, either in the form of 2.5 kg of rice, which is distributed to neighbors in as much as 25 packs, or in the form of shrimp that do not enter the sorting and are distributed to houses around the pond. Even though it can be said that his income has reached nishab. On this basis, the researcher will answer how the legal awareness of vaname shrimp pond farmers in Mojo village, Ulujami District, and Pemalang Regency affects fulfilling zakat obligations and what factors affect the level of legal awareness of vaname shrimp pond farmers in Mojo village in fulfilling zakat obligations. This research is empirical legal research with a qualitative approach. The results showed that the legal awareness of vaname shrimp pond farmers in Mojo Village in fulfilling zakat obligations is relatively low. This is because the farmers of vaname shrimp ponds do not understand the nishab, haul, and amount of zakat. As a result of its expenses, there is no calculation. Factors that affect the level of awareness of vaname shrimp pond farmers in fulfilling this zakat obligation are education, the lack of role of community leaders and the government's role in organizing socialization, and habitual factors.